Prediction of the Performance Characteristics of WEDM on Udimet-L605 Using Different Modelling Techniques. (2017) - Singh Nain, Somvir; Garg, Dixit; Kumar, Sanjeev
Abstract: This paper presents the result of linear, non-linear and ANN-linear regression based modelling technique to determine the surface roughness (SR), waviness (Wa) and material removal rates (MRR) of wire electrical discharge machining (WEDM) on Udimet-L605. One variable at a time approach is used for experimental work considering five level of each input variable. The significance of each model is evaluated based on determinant coefficient (R 2 ), mean square error (MSE) and root mean square error (RMSE) and co-relation coefficient. It was noted that the linear regression modelling provides better prediction of surface roughness and waviness of wire electrical discharge machining on Udimet-L605. ANN-linear regression provides better prediction of the MRR value of WEDM on Udimet-L605.